1980
DOI: 10.1002/j.1537-2197.1980.tb07732.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sulfur Dioxide and Ozone on Growth of Hybrid Poplar Leaves

Abstract: Hybrid poplar plants were exposed to 0.5 ppm SO2, 0.25 ppm O3 or 0.5 ppm SO2 + 0.25 ppm O3, 12 hr/day for 24 days to ascertain their effects on leaf growth and abscission. The data revealed that both O3 alone and O3 + SO2 promoted leaf abscission, while SO2 alone had no effect. Leaf area and dry weight were reduced while leaf abscission was stimulated by ozone fumigation. The interaction found between SO2 and O3, with all the parameters measured, was an antagonistic relationship in which SO2 reduced the toxic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…At the physiological level, net photosynthesis is reduced, dark respiration is increased (Barnes, 1972), and C transport to roots is lowered (McLaughlin and McConathy, 1983). Other physiological impacts include coincident and long-term reductions in stomata1 conductance (Hill and Littlefield, 1969;Reich and Amundson, 1985;Coyne and Bingham, 1982), accelerated leaf senescence (Reich, 1983;Jensen, 1982;Noble and Jensen, 1980;Reich and Lassoie, 1985), reduced root/shoot ratio (Hogsett et al, 1985a;Chappelka and Chevone, 1986), and increased foliar leaching (Rehfuess et al, 1982).…”
Section: Types Of Response Measuresmentioning
confidence: 99%
“…At the physiological level, net photosynthesis is reduced, dark respiration is increased (Barnes, 1972), and C transport to roots is lowered (McLaughlin and McConathy, 1983). Other physiological impacts include coincident and long-term reductions in stomata1 conductance (Hill and Littlefield, 1969;Reich and Amundson, 1985;Coyne and Bingham, 1982), accelerated leaf senescence (Reich, 1983;Jensen, 1982;Noble and Jensen, 1980;Reich and Lassoie, 1985), reduced root/shoot ratio (Hogsett et al, 1985a;Chappelka and Chevone, 1986), and increased foliar leaching (Rehfuess et al, 1982).…”
Section: Types Of Response Measuresmentioning
confidence: 99%
“…Many experiments bave indicated tbat tbe leaves are most sensitive to ozone wben tbey bave just reacbed full size (e.g. Ricb, 1964;Noble & Jensen, 1980). In conifers, tbe greatest ozone sensitivity of current year needles bas been reported to occur several weeks after budbreak, from late spring to early summer (Davis & Wood;1972;Davis & CoppoHno, 1974).…”
Section: Introdl^ctionmentioning
confidence: 99%
“…Noble & Jensen (1980) found that leaves of P. deltoides x trichocarpa appeared sensitive to ozone just prior to attaining their full size, with the result that the growth period was effectively truncated. However, the doses of ozone used in their study were high (250 nil"', 12 h d~') and investigations of the effects of fumigations at more realistic concentrations to not appear to have been attempted.…”
mentioning
confidence: 99%